Activity Pattern Models with Well-Being Indicators. Issue 1 (January 2015) - Carrion, Carlos; Enam, Annesha; Pattabhiraman, Varun; Abou-Zeid, Maya; Ben-Akiva, Moshe
Activity-based travel demand models, particularly a class widely used in practice known as the activity schedule approach, constitute the state of the art in metropolitan travel demand forecasting. In a 2012 paper, Abou-Zeid and Ben-Akiva proposed two extensions to the specification of the activity pattern model in the activity schedule approach. This paper focuses on the econometric extension, which involves adding happiness measurement equations to an activity pattern model to enhance the measurement of utility. This extension is tested with the activity schedule model system and data provided by the Denver Regional Council of Governments in Colorado. Furthermore, a comparison of two criteria—the goodness of fit and the efficiency—of activity pattern models with and without happiness measurement equations is presented. The results indicate that happiness measures enhance the efficiency of the estimates of the activity pattern model.